MOBP and HIP1 in multiple system atrophy: New α‐synuclein partners in glial cytoplasmic inclusions implicated in the disease pathogenesis. (19th January 2021) - Bettencourt, Conceição; Miki, Yasuo; Piras, Ignazio S.; de Silva, Rohan; Foti, Sandrine C.; Talboom, Joshua S.; Revesz, Tamas; Lashley, Tammaryn; Balazs, Robert; Viré, Emmanuelle; Warner, Thomas T.; Huentelman, Matt J.; et al.
Abstract: Aims: Multiple system atrophy (MSA) is a fatal neurodegenerative disease. Similar to Parkinson's disease (PD), MSA is an α‐synucleinopathy, and its pathological hallmark consists of glial cytoplasmic inclusions (GCIs) containing α‐synuclein (SNCA) in oligodendrocytes. We previously identified consistent changes in myelin‐associated oligodendrocyte basic protein ( MOBP ) and huntingtin interacting protein 1 ( HIP1 ) DNA methylation status in MSA. We hypothesized that if differential DNA methylation at these loci is mechanistically relevant for MSA, it should have downstream consequences on gene regulation. Methods: We investigated the relationship between MOBP and HIP1 DNA methylation and mRNA levels in cerebellar white matter from MSA and healthy controls. Additionally, we analysed protein expression using western blotting, immunohistochemistry and proximity ligation assays. Results: We found decreased MOBP mRNA levels significantly correlated with increased DNA methylation in MSA. For HIP1, we found a distinct relationship between DNA methylation and gene expression levels in MSA compared to healthy controls, suggesting this locus may be subjected to epigenetic remodelling in MSA. Although soluble protein levels for MOBP and HIP1 in cerebellar white matter were not significantly different between MSA cases and controls, we found striking differences between MSA and other neurodegenerative diseases, including PD and Huntington's disease. We also found that MOBP and HIP1 are mislocalized into the GCIs in MSA, where they appear to interact with SNCA. Conclusions: This study supports a role for DNA methylation in downregulation of MOBP mRNA in MSA. Most importantly, the identification of MOBP and HIP1 as new constituents of GCIs emphasizes the relevance of these two loci to the pathogenesis of MSA. Abstract : By investigating loci that have shown significant DNA methylation alterations in multiple system atrophy (MSA), this study identified myelin‐associated oligodendrocyte basic protein (MOBP) and huntingtin interacting protein 1 (HIP1) as new constituents of glial cytoplasmic inclusions (highlighted by arrowheads in b and d) and α‐synuclein interactors, thus strengthening the potential role of these two loci in MSA pathogenesis.